Description Parenting Pattern Of Punk Children In District Bojoneogoro - Patonah, Siti; Afandi, Agus Ari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this research is to describe the pattern of parent care in punk children in Bojonegoro District. This research uses descriptive research type with survey approach with sample number 8 parents who have punk children, sampling technique using total sampling. Variable in this research is parent’s parenting pattern in punk child. Methods of data collection by using questionnaires then performed data processing by editing, coding, scoring and tabulating and univariate analysis with frequency distribution. The results obtained more than the majority of respondents (62.5%) implement permissive parenting. In this case it is expected that parents should always pay attention and affection, and supervise and guidance to the child to avoid misbehavior in punk children’s community and apply democratic parenting pattern, where the children are given the opportunity to express their opinions, ideas and wishes so that children participate but there are rules from parents.